(untitled) (Balneo and PRM Research Journal, 2024)
The purpose of this study is to evaluate the functional results one year following anti-VEGF therapy in macular pathology. Material and method: This is a retrospective study that was carried out on a number of 57 patients with macular pathology, out of 108 at Sf. Spiridon Hospital in Iasi. 57 patients with macular pathology were included in the study, respectively 57 eyes, 24 eyes with diabetic macular edema and 33 with neovascular age-related macular degeneration. Eyes in which less than 6 intravitreous injections were performed (less than one year of follow-up), those without oct control examinations and without adequate controls were excluded. Results: Visual acuity improves significantly after treatment both in patients with diabetic macular edema (370 vs 320 microns) and in those with age-related macular degeneration (320 vs 260 microns), while the average thickness of the central macula decreases significantly after treatment. Conclusions: In this study, treatment with intravitreal Aflibercept was associated with improvements in the functional and anatomical outcomes, keeping the increasing trend up to one year of treatment in those who received a minimum of three injections.